The *Congruence Class of the Solutions to a System of Matrix Equations - Yu-Ping Zhang; Chang-Zhou Dong (Journal of Applied Mathematics)
We present the  *congruence class of the least-square and the minimum norm least-square solutions to the system of complex matrix equation AX=C, XB=D by generalized singular value decomposition and canonical correlation decomposition.